Impact of Self-Management Clustered Care on Psychological and Birth Outcomes in Gestational Diabetes - Tang S; Wang S; Wu J; Hu S; Lu T; Zhu M; Li J; Xue F (International Journal of Women's Health)
Shuting Tang,1,* Song Wang,1,* Jinyan Wu,1 Shoudi Hu,1 Tingting Lu,2 Minli Zhu,2 Jinzhi Li,1 Fang Xue1 1School of Nursing, Bengbu Medical University, Bengbu, Anhui, People’s Republic of China; 2Maternity Ward, the First Affiliated Hospital of Bengbu Medical University, Bengbu, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Xue, School of Nursing, Bengbu Medical University, No. 2600 Donghai Avenue, Bengbu, Anhui, People’s Republic of China, Email 0700036@bbmu.edu.cnPurposes: To investigate the effects of a self-management-cluster-based pregnancy care model (SMB-CPCM) on the psychological status and delivery outcomes of pregnant women with gestational diabetes mellitus (GDM).Patients and Methods: A total of 120 pregnant women with GDM who had been filed and had regular obstetric examinations in a tertiary-level hospital in Bengbu City between 1 April 2023 and 1 April 2024 were included in the study using the convenience sampling method. Sixty women each were grouped into a study group and a control group using the randomised numeric table method. The study group implemented the SMB-CPCM and the control group used the conventional pregnancy healthcare model. We compared the differences in self-management ability, blood glucose concentration, delivery outcome, and psychological status.Results: Self-management ability scores were higher in both groups following the intervention than before the intervention (P< 0.001), and the increase was more notable in the study group (t=9.237, P< 0.001). Anxiety scale (63.31± 4.73, 48.29± 4.20) and depression self-assessment scale scores(60.70± 3.49, 41.69± 4.76) in the study group were lower after the intervention than before the intervention(t=13.322, 18.115, P< 0.001). Following the intervention, fasting blood glucose(5.39± 0.42, 4.92± 0.45) and postprandial 2-h blood glucose(6.70± 0.71, 5.92± 0.64) exhibited a reduction compared to the pre-intervention period (P< 0.001). Furthermore, this decline was more pronounced in the study group (t=4.267, 4.584, P< 0.001). The study group demonstrated an elevated spontaneous delivery rate compared to the control group (χ2=5.168, P< 0.05). Additionally, the rates of gestational hypertension (χ2=4.941), pre-term labour (χ2=3.890), and macrosomia (χ2=4.050) were reduced in the study group when compared to the control group (P< 0.05).Conclusion: SMB-CPCM can effectively control the blood glucose levels of pregnant women with GDM and improve their self-management ability, psychological status, and delivery outcomes. SMB-CPCM shows a good prospect in the management of gestational diabetes and is worth promoting. Future research can explore the impact of SMB-CPCM on long-term health outcomes of pregnant women with diabetes, so as to comprehensively evaluate its clinical value.Keywords: clustered pregnancy care model, gestational diabetes, self-management ability, delivery outcomes, psychological state